Characterization, dissolution and solubility of lead fluorapatite at 25-45 °C. (September 2020) - Yan, Qiming; Zhu, Yinian; Feng, Guojie; Zhu, Zongqiang; Zhang, Lihao; Liu, Jie; He, Hao
Abstract: Lead is harmful to living organisms. The substitution of Ca 2+ in Calcium fluorapatite by Pb 2+ can cause the forming of lead fluorapatite (Pb-FAP). The solubility data of Pb-FAP are significant in geoscience. Unfortunately, the solubility product and thermodynamic data for Pb-FAP in water under different conditions are lacking. In this study, the synthesized Pb-FAP was dissolved at initial pH of 2.00, 5.60, and 9.00. The pH was adjusted with HNO3 and NaOH, and the dissolution temperatures were set as 25, 35, and 45 °C. The characterizations showed the Pb-FAP nanorods were generally kept stable during the experiment. When the temperature was 25 °C and the initial pH = 2.00, both the concentrations of lead and phosphate in the solution increased rapidly, and reached a steady state at 4320 h and 5040 h, respectively, whereas the fluoride concentration reached the peak value within 1 h and achieved a stable state after 3600 h. The Pb/P molar ratio increased constantly from 2.07 to 2.13, which was slightly higher than the stoichiometric ratio of 1.67. And then the ratio decreased to 1.55 at the end of the experiment. When the initial pH 5.60 and 9.00 (the temperature was fixed at 25 °C for both experiments), the final pH values of the solution were 3.53 and 3.68 after 5040 h at the end of the experiment, respectively. The solubility product constants for Pb-FAP ( K sp ) were 10 −78.29 (10 −78.19 -10 −78.44 ) at 25 °C, 10 −77.37 (10 −77.25 -10 −77.43 ) at 35 °C and 10 −76.62 (10 −76.54 -10 −76.70 ) at 45 °C, respectively. Based on the lg K sp values obtained at an initial pH of 2.00 and 25 °C, the Gibbs free energy of formation for Pb-FAP was calculated to be −3904.01 kJ mol −1 (−3903.43 to −3904.86 kJ mol −1 ). Graphical abstract: The dissolution mechanism of lead fluorapatite. Step 1. Adorption H + from aqueous to Pb-FAP surface.Step 2. Pb 2+, PO4 3- and F − relesed from the Pb-FAP surface to solution.Step 3. Pb 2+, PO4 3- and F − adsorbed onto Pb-FAP surface backward.Step 4. The dissolution of Pb-FAP reached stable state. Image 1 Highlights: One of the apatite solid solution named lead fluorapatite was synthetized. The lead fluorapatite was typical hexagonal crystals with favorable stability. The solubility products for lead fluorapatite (lgKsp ) was −78.29 to −76.62 at 25–45 °C. The Gibbs free energy of formation for lead fluorapatite was −3904.01 kJ mol −1 .